Formación: violencia comunicacional y vida - Sobrino Chunga, Lisle (2013)
The following article is about the necessityof attending communication levels duringchild training and that care and respect, forthe manners how are stared the interactions,should come from all components of eachfamily, nevertheless, not only of them but alsoof each person that has access, as carer orcompanion within the home.